Warming impacts on photosynthetic processes in dominant plant species in a subtropical forest. Issue 2 (8th March 2022) - Aspinwall, Michael J.; Chieppa, Jeff; Gray, Eve; Golden‐Ebanks, Morgan; Davidson, Lynsae
Abstract: Climate warming could shift some subtropical regions to a tropical climate in the next 30 years. Yet, climate warming impacts on subtropical species and ecosystems remain unclear. We conducted a passive warming experiment in a subtropical forest in Florida, USA, to determine warming impacts on four species differing in their climatic distribution, growth form, and functional type: Serenoa repens (palm), Andropogon glomeratus (C4 grass), Pinus palustris (needled evergreen tree), and Quercus laevis (broadleaved deciduous tree). We hypothesized that warming would have neutral‐positive effects on photosynthetic processes in monocot species with warmer climatic distributions or adaptations to warmer temperatures, but negative effects on photosynthesis in tree species. We also hypothesized that periods of low soil moisture would alter photosynthetic responses to warming. In both monocot species, warming had no significant effect on net photosynthesis ( A ) or stomatal conductance ( g s ) measured at prevailing temperatures, or photosynthetic capacity measured at a common temperature. In P . palustris, warming reduced A (−15%) and g s (−28%), and caused small reductions in Rubisco carboxylation and RuBP regeneration. Warming had little effect on photosynthetic processes in Q . laevis . Interestingly, A . glomeratus showed little sensitivity to reduced soil moisture, and all C3 species reduced A and g s as soil moisture declined and did so consistently across temperature treatments. In subtropical forests of the southeastern US, we conclude that climate warming may have neutral or slightly positive effects on the performance of grasses and broadleaved species but negative effects on P . palustris seedlings, foreshadowing possible changes in community and ecosystem properties.